(3LhGgQ GdHjGf aj OhdI Bd YKeGfs - (3CMeO Hf bQg ceGd GdGhOj, CHj GdajVs
(3ChdgG (B:s
(3fMeOc Gddge Ydi eG CXgQJ CSQGQc ai GdchGcH hGdfLhe deG GbJQM Ydi HGdSDGd Cf CLeY dg GdbhGYO Gdcdjg GdLdjI s
(3BNQgG (B:s
(3bGd GdeDda TaGg Gddg ef GdMei GdHGQOI (B: (3LeYJ gPG GdcJGH hGfG ef Chd jhe GHJOCJ ajg Edi LJeI eMehe s
(3GdJhKjbGJ GdeQLYjI (B:s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B125 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B3 - (3U (B131 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdaGJjcGf (B(870) s
Keywords: (3GdJGQjNs